APPLYING VLOG IN TEACHING VOCABULARY - Nur Ina Syam; Emirati Emirati (Universitas Muhammadiyah Makassar, 2021)
The aim of this study is to find out whether or not the use of vlog will enhance the vocabulary of the students. This study used pre-experimental studies consisting of pre-test, treatment, and post-test. The participants in the study were 25 students of the second grade students of Universitas Muhammadiyah Bulukumba. Based on the findings of the study, there is a substantial difference between the mean pre-test score and the mean post-test score, from a very bad classification to a decent classification. In addition, the t-test value of this analysis (16,12) is greater than the t-table value (3,745) with a degree of significance of 0,05. It means that it supports the alternative hypothesis.